Butoh-Ballet - Job, Jacqueline Felicity (School of Dance, 2015)
This dissertation explores intercultural theory through an investigation of butoh methods that shift performance processes of ballet. Theories of Post colonialism and Performance have been interrogated and applied to distill a theme, Butoh-Ballet. A qualitative research approach was undertaken for this study following a short series of dance workshops in butoh carried out on four members of Cape Town City Ballet company, in Cape Town, in 2013. This dissertation will show how butoh could contribute to overcoming colonial constructs, which have penetrated all spheres of South African society including Dance and its discourse. Dance research is fairly new in South Africa and largely situated within Contemporary dance. Ballet in South Africa has received relatively less critical analysis. The dissertation is particularly focused on expanding worldviews beyond a Eurocentric bias. Feminist notions as explicated by Ketu Katrak and Rustom Bharucha are considered in parallel to the philosophies of Maurice Merleau-Ponty. I also borrowed from Gayatri Spivak's notion of 'decolonising the imagination', to suggest that butoh may provide a means for ballet to re-imagine the body and its performance. This study acknowledges my subjective, 'endarkened' voice that emanates from my hybrid identity as Coloured, woman, pioneer Butoh artist, in postapartheid South Africa. I have proposed that butoh balances an external focus of the body found in ballet, with a more spiritually nuanced approach found in butoh. My argument hopefully marks the earliest reflective analysis of the subtle shifts butoh could make to ballet in South Africa today.